2022
DOI: 10.3389/fviro.2022.971293
|View full text |Cite
|
Sign up to set email alerts
|

Altered recruitment of Sp isoforms to HIV-1 long terminal repeat between differentiated monoblastic cell lines and primary monocyte-derived macrophages

Abstract: Human immunodeficiency virus type 1 (HIV-1) transcription in cells of the monocyte-macrophage lineage is regulated by interactions between the HIV-1 long terminal repeat (LTR) and a variety of host cell and viral proteins. Binding of the Sp family of transcription factors (TFs) to the G/C box array of the LTR governs both basal as well as activated LTR-directed transcriptional activity. The effect of monocytic differentiation on Sp factor binding and transactivation was examined with respect to the HIV-1 LTR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…About two decades ago, a study in Jurkat T cells postulated a correlation between Vpr’s abilities to transactivate the LTR and cause G2 arrest [ 53 ]. Since then, multiple other studies on this topic have been carried out on immortalized cell lines, including T cell-derived models, where it was observed that Vpr-dependent transactivation relies on its capacity to recruit various isoforms of the Sp transcription factor family to the LTR [ 54 , 55 , 56 ], although this effect proved highly cell type-dependent. Only in 2019 did the work of Hotter and collaborators finally demonstrate the importance of Sp1 availability towards viral expression in the context of CD4 + T cells, though the role of Vpr in this process was not assessed in their study [ 57 ].…”
Section: Viral Genome Transcription and G2 Cell Cycle Arrestmentioning
confidence: 99%
“…About two decades ago, a study in Jurkat T cells postulated a correlation between Vpr’s abilities to transactivate the LTR and cause G2 arrest [ 53 ]. Since then, multiple other studies on this topic have been carried out on immortalized cell lines, including T cell-derived models, where it was observed that Vpr-dependent transactivation relies on its capacity to recruit various isoforms of the Sp transcription factor family to the LTR [ 54 , 55 , 56 ], although this effect proved highly cell type-dependent. Only in 2019 did the work of Hotter and collaborators finally demonstrate the importance of Sp1 availability towards viral expression in the context of CD4 + T cells, though the role of Vpr in this process was not assessed in their study [ 57 ].…”
Section: Viral Genome Transcription and G2 Cell Cycle Arrestmentioning
confidence: 99%